2016
DOI: 10.1097/md.0000000000002293
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Parkinson's Disease in Patients With Obstructive Sleep Apnea

Abstract: Obstructive sleep apnea (OSA), characterized by repetitive episodes of apnea/hypopnea and hypoxia, is associated with systemic inflammation and induces metabolic, endocrine, and cardiovascular diseases. Inflammation might have an impact on neurodegenerative diseases. This study investigates the possible association between OSA and Parkinson's disease (PD). Random samples out of 1 million individuals were collected from Taiwan's National Health Insurance database. A total of 16,730 patients with newly diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…OSA and PD often coincide with one another, whether due to the high general prevalence of OSA, the higher incidence of OSA in PD, or OSA predisposing to PD. In large-scale population studies with long follow-up periods, OSA has been suggested to increase the incidence of PD [5]. Our group has found an association between OSA and PD nonmotor symptoms [6], which improved with OSA treatment [7].…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…OSA and PD often coincide with one another, whether due to the high general prevalence of OSA, the higher incidence of OSA in PD, or OSA predisposing to PD. In large-scale population studies with long follow-up periods, OSA has been suggested to increase the incidence of PD [5]. Our group has found an association between OSA and PD nonmotor symptoms [6], which improved with OSA treatment [7].…”
Section: Introductionsupporting
confidence: 53%
“…However, OSA may also, in turn, have adverse effects on PD. In support of this, large population studies have suggested that pre-existing OSA predisposes to PD [5]. Conversely, a multicenter study from the International RBD Study Group found OSA not to be a risk factor for subsequent development of PD among idiopathic RBD patients, although OSA scoring criteria were not standardized or defined and likely differed between centres, making conclusions on OSA less reliable [19].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies that employed well-selected controls revealed similar prevalence of OSA in PD and general population (82, 83). Interestingly, three studies have suggested an increased risk of PD among patients with OSA with hazard ratios (HR) of 1.37, 1.84 and 2.26, respectively (8486). Although the risks are higher, the absolute numbers remain low, and thus OSA might overall provide a minor risk for subsequent development of PD (84).…”
Section: Introductionmentioning
confidence: 99%
“…The adjusted HR for developing Parkinson's disease in people with OSA was 1.37 (95% CI 1.12 to 1.68, p<0.05). The absolute incidence of Parkinson's disease in the OSA group was 2.30/1000 person-years, compared with 1.71 in controls 49. The authors speculate on the possible mechanisms for this association: there is evidence that OSA induces systemic inflammatory responses as well as brain hypoperfusion that, by increasing oxidative stress, could lead to various pathogenic effects, including accelerated degeneration of dopaminergic neurones in the substantia nigra.…”
Section: Osa and Idiopathic Parkinson's Diseasementioning
confidence: 92%